Improving the Standardization of Human Resource Quality in Clinical Services - Gultom, Christa Natalia; Desideria Yosepha Ginting; Bambang Sumantri; Agustatius Sitepu (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Health Human Resources (HRH) include professional health workers, strategic personnel, non-professional staff, and supporting personnel who contribute to healthcare management and delivery to achieve the highest possible standard of public health. The quality of HRH is a key determinant of healthcare service quality, particularly at the clinic level. Objectives: To assess the quality of HRH at Santa Maria Palipi Clinic, identify the barriers to improving HRH quality, and describe the efforts made to enhance HRH standards. Research Methods: This study employed a descriptive qualitative approach involving 15 informants: 2 key informants, 6 staff members of Santa Maria Palipi Clinic, and 7 patients or their families. Data were collected through observation and in-depth interviews. Results: The study found that the quality of HRH at Santa Maria Palipi Clinic has not fully met the established standards. Major challenges include difficult-to-change individual characteristics, lack of compliance with existing regulations, limited personnel, and poor collaboration among clinic staff. Efforts to address these issues include regular evaluations and training provided by both the clinic leadership and supporting foundations. Conclusion: Santa Maria Palipi Clinic must continue to improve HRH quality to meet service standards. Strong commitment, continuous training, and better teamwork among health workers are essential strategies for enhancing healthcare service quality.